Service fanatics : how to build superior patient experience the Cleveland Clinic way - Merlino, James (McGraw-Hill's AccessMedicine., 2015)
"Rather than view patients simply as sick people who need treatment, Cleveland Clinic sees them also as important stakeholders in the organization's success. Patients are customers--who desire, pay for, and deserve the best possible care and experience during what is often a challenging time in their lives. Featuring customer service case studies, as well as invaluable insight from C-level executives at top corporations in various industries, Service Fanatics provides actionable lessons for any manager and business leader beyond healthcare. Whether you run a healthcare institution, nonprofit, or for-profit business, Service Fanatics will help you create the kind of customer experience that promises to transform your organization into an industry powerhouse."--Unedited summary from book